A noble interaction: An assessment of noble gas binding ability of metal oxides (metal = Cu, Ag, Au). Issue 13 (4th April 2016) - Pan, Sudip; Saha, Ranajit; Kumar, Anand; Gupta, Ashutosh; Merino, Gabriel; Chattaraj, Pratim K.
Abstract : An in silico study is performed on the structure and the stability of noble gas (Ng) bound MO complexes (M = Cu, Ag, Au). To understand the stability of these Ng bound complexes, dissociation energies, dissociation enthalpy, and dissociation free energy change are computed. The stability of NgMO is also compared with that of the experimentally detected NgMX (X= F, Cl, Br). It is found that MO has lower Ng binding ability than that of MX. All the dissociation processes producing Ng and MO are endothermic in nature and for the Kr‐Rn bound MO (M = Cu, Au), and Xe and Rn bound AgO cases, the corresponding dissociation processes are turned out to be endergonic in nature at standard state. The Wiberg bond indices of NgM bonds and Ng→M electron transfer gradually increase from Ar to Rn and for the same Ng they follow the order of NgAuO > NgCuO > NgAgO. Energy decomposition analysis shows that the NgM bonds in NgMO are partly covalent and partly electrostatic in nature. Electron density analysis further highlights the partial covalent character in NgM bonds. © 2016 Wiley Periodicals, Inc. Abstract : The nature of the interaction between noble metals and noble gasses has been at the center of a lively debate. The noble gas binding ability of noble metal (Cu, Ag, Au) oxides is explored by employing high‐level ab initio methods. The stability of noble gas bound metal oxides are very comparable to that of experimentally detected noble gas bound noble metal halides.